(untitled) (Analele Universității București.Filosofie, 2025)
The paper addresses the variety of human types and attitudes facing the unknown and their philosophical implications and connections with philosophy of knowledge and philosophy of conscience and consciousness. Philosophically, the human attitude in front of the unknown dwells at the boundary between the known and the unknown. This boundary could be the equivalent of the horizon of mystery in the philosophy of Lucian Blaga, a boundary that differs greatly from one human type to another. In order to more clearly differentiate the various human types, a scheme is proposed based on different attitudes related to three tendencies to know, respectively to accept reality, as it is perceived by each. The three so-called axes are: Positivism/Negativism, Curiosity/Fear, Openness/Isolation. It results in 12 types of philosophical attitudes against the unknown that are presented and analysed. This representation is interpreted in correlation to Blaga’s imaginative exercise of conceiving philosophical consciousness as a prism inscribed in a sphere representing the totality of everything (the totality of existence, the universe). Other aspects pertaining the correlations between this description of the 12 types of philosophical attitudes against the unknown and the philosophy of man in Lucian Blaga are emphasized, too.